(NlITERATURA (BXIX (NWEKAs (Nu^EBNIKs - (NsAHAROW w(B. (Ni(B.s; (NzININ s(B.(Na(B.s ((NmOSKWAs (NrUSSKOE SLOWOs, 2007)
(Nu^EBNIK ZNAKOMIT U^A]IHSQ S ZOLOTYM WEKOM RUSSKOJ LITERATURY RASSMATRIWAEMOJ KAK WYSOKOE GUMANISTI^ESKOE I PATRIOTI^ESKOE EDINSTWO(B.s
Keywords: (Nu^EBNIKs